Penyuluhan DAGUSIBU sebagai upaya peningkatan pengetahuan masyarakat Desa Sukadana Lombok Tengah terkait penggunaan dan pengelolaan obat yang rasional menggunakan metode CBIA - Alfan Fauzi; Candra Eka Puspitasari; Nadya Arianita Turisia (Universitas Mataram, 2022)
The lack of health facilities and personnel compared to the population in Sukadana Village makes public knowledge about drug information and self-medication is still very low. Drug information including how to get, use, store and dispose of drugs properly is known as DAGUSIBU. This DAGUSIBU counseling aims to increase the knowledge of the Sukadana village community regarding the rational use and management of drugs. This counseling had been carried out through the delivery of material by pharmacists and continued with practice using the Community Based Interactive Approach Method (CBIA). After the DAGUSIBU counseling was carried out, the community's knowledge about drugs and self-medication had increased compared to the knowledge before the counseling.